Role of Anticonvulsant and Antiepileptogenic Neurosteroids in the Pathophysiology and Treatment of Epilepsy - Reddy, D. Samba (Frontiers in Endocrinology, 2011)
This review highlights the role of major endogenous neurosteroids in seizure disorders and the promise of neurosteroid replacement therapy in epilepsy. Neurosteroids are endogenous modulators of seizure susceptibility. Neurosteroids such as allopregnanolone (3a-hydroxy-5a-pregnane-20-one) and allotetrahydrodeoxycorticosterone (3a,21-dihydroxy-5a-pregnan-20-one) are positive modulators of GABA-A receptors. Aside from peripheral tissues, neurosteroids are synthesized within the brain, mostly in principal neurons. Neurosteroids potentiate synaptic GABA-A receptor function and also activate delta-subunit-containing extrasynaptic GABA-A receptors that mediate tonic currents and thus may play an important role in neuronal network excitability and seizure susceptibility. Our studies over the past decade have shown that neurosteroids are broad-spectrum anticonvulsants and confer seizure protection in various animal models. They protect against seizures induced by GABA-A receptor antagonists, 6-Hz model, pilocarpine-induced limbic seizures and seizures in kindled animals. Unlike benzodiazepines, tolerance does not occur to their actions during chronic administration. Our recent studies provide compelling evidence that neurosteroids may have antiepileptogenic properties. There is emerging evidence that endogenous neurosteroids may play a key role in the pathophysiology of catamenial epilepsy, stress-sensitive seizure conditions, temporal lobe epilepsy, and alcohol-withdrawal seizures. It is suggested that neurosteroid replacement with natural or synthetic neurosteroids may be useful in the treatment of epilepsy. Synthetic analogs of neurosteroids that are devoid of hormonal side effects show promise in the treatment of diverse seizure disorders. Agents that stimulate endogenous production of neurosteroids may also be useful for treatment of epilepsy.